Tendências regionais da indústria brasileira no Século XXI - Clélio Campolina Diniz; Philipe Scherrer Mendes (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– Throughout this article, we analyze and discuss the main trends in recent locational patterns of Brazilian industry. Taking into account the overall economic growth as well as in the industry sector since the beginning of XXI century, many structural changes related to the occurrence of simultaneous process like industrialization and deindustrialization are worth of analyzing. In fact, to understand the new changes in locational patterns of industry activities, we claimed here that it will be required to recognize among others: accelerated rhythms of technical and organizational changes; the increasing share of service sector in the economy; the dynamics of agricultural frontiers; the impact of public policies especially those from social policies; and the results of investments in infrastructure driven for energetic purposes.
Keywords: I28; H75; C21; 330; industrialization; deindustrialization; industry locational patterns; regional development